2018
DOI: 10.1128/jb.00176-18
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila Is Directly Sensitive to 2-Deoxyglucose-Phosphate via Its UhpC Transporter but Is Indifferent to Shifts in Host Cell Glycolytic Metabolism

Abstract: Toll-like receptor (TLR) stimulation induces a pronounced shift to increased glycolytic metabolism in mammalian macrophages. We observed that bone marrow-derived macrophages (BMMs) increase glycolysis in response to infection with , but the role of host macrophage glycolysis in terms of intracellular replication is not currently understood. Treatment with 2-deoxyglucose (2DG) blocks replication in mammalian macrophages but has no effect on bacteria grown in broth. In addition, we found that 2DG had no effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 44 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…In an attempt to identify specific factors that explain the ability of IFNγ to restrict L. pneumophila replication in macrophages to specific genetic factors associated with the immune response, we tested the ability of IFNγ to restrict L. pneumophila in BMMs derived from various knockout mice. Using an extensively validated strain of Δ flaA L. pneumophila that expresses luminescence (lux) genes from P. luminescens (20, 3638), we confirmed that Δ flaA L. pneumophila replicates in unstimulated BMMs but does not replicate in BMMs stimulated with IFNγ ( Figure 1A ). As expected, BMMs lacking the IFNγ receptor ( Ifngr −/− ) do not restrict L. pneumophila replication in the presence of IFNγ ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…In an attempt to identify specific factors that explain the ability of IFNγ to restrict L. pneumophila replication in macrophages to specific genetic factors associated with the immune response, we tested the ability of IFNγ to restrict L. pneumophila in BMMs derived from various knockout mice. Using an extensively validated strain of Δ flaA L. pneumophila that expresses luminescence (lux) genes from P. luminescens (20, 3638), we confirmed that Δ flaA L. pneumophila replicates in unstimulated BMMs but does not replicate in BMMs stimulated with IFNγ ( Figure 1A ). As expected, BMMs lacking the IFNγ receptor ( Ifngr −/− ) do not restrict L. pneumophila replication in the presence of IFNγ ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 67%
“…We next investigated the possibility that IFNγ may act to restrict L. pneumophila not through induction of any single antimicrobial factor but by changing the metabolic landscape of the host macrophage to be unsuitable for the metabolic needs of L. pneumophila . As macrophages infected with L. pneumophila and IFNγ-stimulated macrophages increase rates of glycolysis (1, 36, 42), we tested whether treatment with the glycolysis inhibitor 2-deoxyglucose (2DG) might interfere with IFNγ-dependent restriction observed in BMMs. 2DG is metabolized to 2DG-phosphate in cells, which is directly antimicrobial (36).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations